Faktor-Faktor Risiko yang Memprediksi Kematian Satu Tahun Pertama Pasien Gagal Ginjal Kronik dengan Hemodialisis di RS Sumber Waras Periode 2018-2019 - Ronald Winardi Kartika; Fanny Indarta; Hardianti (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Chronic Kidney Disease (CKD) is a global public health problem where the prevalence and incidence of CKD is increasing every year. According Indonesian Renal Registry in 2016 , about 60% of CKD underwent dialysis in the form of hemodialysis (98%) and peritoneal dialysis (2%). The deaths of hemodialysis patients during 2015 were 1,243 people with the most cause of death is cardiovascular (41%), and unknown (30%). The purpose of this study was to determine the causes of death in the first year of CKD patients undergoing hemodialysis. This study was a descriptive and analytic study with a cross sectional approach. Collecting data by looking at the patient's medical record. The number of samples is 46 people, the sample uses the total sampling method. Univariate data analysis to see the distribution of patient profiles, bivariate analysis with Chi square test and multivariate analysis using logistic regression to see the relationship between variables. The results of the analysis showed that the factors associated with death in the first year of kidney failure patients undergoing hemodialysis were age (p=0.03) and vascular access (p=0.000). The first year of chronic renal failure patients undergoing hemodialysis is age and vascular access.